A State of Play British Politics on Screen, Stage and Page, from Anthony Trollope to The Thick of It - Fielding, Steven (Bloomsbury Academic, 2014)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. A State of Play explores how the British have imagined their politics, from the parliament worship of Anthony Trollope to the cynicism of The Thick of It. In an account that mixes historical with political analysis, Steven Fielding argues that fictional depictions of politics have played an important but insidious part in shaping how the British think about their democracy and have helped ventilate their many frustrations with Westminster. He shows that dramas and fictions have also performed a significant role in the battle of ideas, in a way undreamt of by those who draft party manifestos. The book examines the work of overtly political writers have treated the subject, discussing the novels of H.G. Wells, the comedy series Yes, Minister and the plays of David Hare. However, it also assesses how less obvious sources, such as the films of George Formby, the novels of Agatha Christie, the Just William stories and situation comedies like Steptoe and Son, have reflected on representative democracy. A State of Play is an invaluable, distinctive and engaging guide to a new way of thinking about Britain's political past and present.